2013
DOI: 10.1177/1934578x1300800332
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Anti-Trypanosoma cruzi Activity of Essential Oils Obtained from Leaves of Xylopia frutescens and X. laevigata (Annonaceae)

Abstract: Essential oils from leaves of Xylopia frutescens (XFMJ) and two specimens of Xylopia laevigata (XLMC and XLSI) were obtained by hydrodistillation using a Clevenger-type apparatus, and analyzed by GC-MS and GC-FID. Sesquiterpenes dominated the essential oils. The main constituents of XFMJ were (E)-caryophyllene (24.8%), bicyclogermacrene (20.8%), germacrene D (17.0%), -elemene (7.9%), and (E)--ocimene (6.8%). XLMC contained significant quantities of germacrene D (18.9%), bicyclogermacrene (18.4%), -elemene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Although the essential oils were less effective than benznidazole or mefloquine in the biological assays, it is important to say that these reference drugs are highly toxic to hosts and showing a variable efficacy in several strains that have some degree of resistance to these drugs (18,19). Furthermore, results presented in this study are considered very promising when compared with other results of Annonaceae essential oils with trypanocidal and antimalarial activity (6,16,20). Journal of Essential Oil Research 5 After confirming that AVOE and ASOE were able to kill parasites, our next step was to understand how they affect parasite cells through assays with trypomastigotes forms of T. cruzi, once the trypanocidal activity of species of Annonaceae is better documented than the antimalarial activity.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Although the essential oils were less effective than benznidazole or mefloquine in the biological assays, it is important to say that these reference drugs are highly toxic to hosts and showing a variable efficacy in several strains that have some degree of resistance to these drugs (18,19). Furthermore, results presented in this study are considered very promising when compared with other results of Annonaceae essential oils with trypanocidal and antimalarial activity (6,16,20). Journal of Essential Oil Research 5 After confirming that AVOE and ASOE were able to kill parasites, our next step was to understand how they affect parasite cells through assays with trypomastigotes forms of T. cruzi, once the trypanocidal activity of species of Annonaceae is better documented than the antimalarial activity.…”
Section: Resultsmentioning
confidence: 62%
“…Recently, Costa et al (6) described the chemical composition of the essential oil from the leaves of AVOE, identifying eighteen compounds less than this study. These variations, or detector sensitivity or sample dilution in the composition of the major constituents, as well as the contents of all components, can be related to soil and climate conditions, water stress, collection place, nutrition and other abiotic factors (16). Although limonene, (Z)-β-ocimene, linalool, δ-elemene, α-copaene, α-gurjenene, and dehydro-aromadendrene that contributes to the chemical knowledge of the essential Note: RI a (calc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although popular uses of this plant are almost unknown, we found that a decoction of its leaves and flowers is used in the folk medicine of the Brazilian Northeast for several purposes, including painful disorders, heart disease, treating tumors, and inflammatory conditions [1]. Previous phytochemical investigations of this species reported the presence of terpenes [2], essential oils [1,3,4,5], and alkaloids [6], which presented larvicidal [2], antimicrobial [2], antioxidant [3], antitumor [1], tripanocidal [3,4], anti-inflammatory [5], and antinociceptive properties [5]. Herein, the chemical composition and cytotoxicity of the essential oil obtained from the fresh fruits of X. laevigata were investigated for the first time.…”
mentioning
confidence: 95%